2009
DOI: 10.1091/mbc.e09-05-0377
|View full text |Cite
|
Sign up to set email alerts
|

The Nup107-160 Nucleoporin Complex Promotes Mitotic Events via Control of the Localization State of the Chromosome Passenger Complex

Abstract: The human Nup107-160 nucleoporin complex plays a major role in formation of the nuclear pore complex and is localized to kinetochores in mitosis. Here we report that Seh1, a component of the Nup107-160 complex, functions in chromosome alignment and segregation by regulating the centromeric localization of Aurora B and other chromosome passenger complex proteins. Localization of CENP-E is not affected by Seh1 depletion and analysis by electron microscopy showed that microtubule kinetochore attachments are intac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
86
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 73 publications
(100 reference statements)
6
86
0
Order By: Relevance
“…In Xenopus egg extracts and mammalian tissue culture cells, a fraction of the Nup107 complex that includes Seh1 targets to kinetochores, spindles and/or spindle poles from early prometaphase through early anaphase (Belgareh et al, 2001;Orjalo et al, 2006). Moreover, reducing the levels of Nup107-160 components disrupts spindle assembly and cytokinesis (Aitchison et al, 1995;Bai et al, 2004;Mishra et al, 2010;Orjalo et al, 2006;Platani et al, 2009;Zuccolo et al, 2007). Importantly, the specific depletion of seh1 results in the failure of the Nup107 complex to target to kinetochores at mitosis and results in multiple mitotic defects (Zuccolo et al, 2007;Platani et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Xenopus egg extracts and mammalian tissue culture cells, a fraction of the Nup107 complex that includes Seh1 targets to kinetochores, spindles and/or spindle poles from early prometaphase through early anaphase (Belgareh et al, 2001;Orjalo et al, 2006). Moreover, reducing the levels of Nup107-160 components disrupts spindle assembly and cytokinesis (Aitchison et al, 1995;Bai et al, 2004;Mishra et al, 2010;Orjalo et al, 2006;Platani et al, 2009;Zuccolo et al, 2007). Importantly, the specific depletion of seh1 results in the failure of the Nup107 complex to target to kinetochores at mitosis and results in multiple mitotic defects (Zuccolo et al, 2007;Platani et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…4D-F). In mammalian cells, reducing the levels of Seh1, or other Nup107-160 complex members, results in spindle defects and mitotic delay (Mishra et al, 2010;Platani et al, 2009;Zuccolo et al, 2007). Additionally, Xenopus egg extracts depleted of Nup107-160 complex members have a reduced ability to assemble bipolar spindles (Mishra et al, 2010;Orjalo et al, 2006).…”
Section: 15mentioning
confidence: 99%
See 1 more Smart Citation
“…Its dephosphorylation and subsequent deactivation presumably allows the abscission machinery to facilitate abscission. 6,16,17 Depletion of other NPC components including the protein ELYS, a putative transcription factor, or members of the Nup107/160 complex (Nup107, Seh1 and Nup133) also results in an increase in cytokinetic cells, 18,19 however it is unknown if this delayed abscission is due to incomplete NPC reassembly and persistent aurora B activation.…”
Section: Introductionmentioning
confidence: 99%
“…This specific role for nup107 may explain its apparently stronger expression in our in situs, since it plays more than a structural role in a single subcomplex. In another study, seh1 was shown to be necessary for correct chromosome alignment in mitosis and for completion of cytokinesis (Platani et al, 2009). This suggests that in addition to the role that the 107-160 subcomplex has as a unit, individual members of the subcomplex also have unique functions.…”
Section: Discussionmentioning
confidence: 99%